Financial management practices: inefficiencies for self-sustainable on donor funded water projects the case study of global water initiatives program phase 1 - Mapunda, K.N (Mzumbe University, 2024)
A dissertation submitted in partial fulfilment of the requirements for award of the degree of Master of Science in Accounting and Finance(Msc-A&F) of Mzumbe University